A dissolving and glucose-responsive insulin-releasing microneedle patch for type 1 diabetes therapy. Issue 3 (11th December 2020) - Zhang, Yujie; Wu, Mingxin; Tan, Di; Liu, Quan; Xia, Re; Chen, Min; Liu, Yuangang; Xue, Longjian; Lei, Yifeng
Abstract : A dissolving microneedle patch for responsive insulin release and type 1 diabetes therapy. Abstract : Diabetes and its complications have become crucial public health challenges worldwide. In this study, we aim to develop a dissolving and glucose-responsive insulin-releasing microneedle (MN) patch system, for minimally invasive and glucose-responsive insulin delivery for type 1 diabetes therapy. The MNs were composed of dissolving and biodegradable gelatin and starch materials, which encapsulated glucose-responsive insulin-releasing gold nanocluster (AuNC) nanocarriers. The fabricated MNs had a complete and uniform structure, consisting of an array of 11 × 11 conical needles, with a needle height of 756 μm, a bottom diameter of 356 μm, a tip diameter of 10 μm, and a tip-to-tip distance of 591 μm. The encapsulated AuNC nanocarriers as additives in the MNs enhanced the mechanical strength of the MNs, and facilitated the penetration of the MNs into the skins of mice. Moreover, the AuNC nanocarrier drugs in the MNs enabled MN patches with a glucose-responsive insulin releasing behavior. With one transdermal application of MN patches on the dorsal skin of mice, the MN patches effectively regulated the BG levels of mice in normoglycemic ranges for 1 to 2 days, and effectively alleviated the diabetic symptoms in type 1 diabetic mice. This dissolving and glucose-responsive insulin-releasing MN patch system realized a closed-loop administration of insulin with minimal invasion, providing great potential applications for type 1 diabetes therapy.